Dating the birth, growth and death of Miocene carbonate platforms in the South China Sea, Central Luconia Province, Sarawak - K Ting, BJ Pierson, M Pubellier, D Menier, G Warrlich, S Jamalud, . (2012)
The regional distribution, respective location of the Miocene carbonate platforms of Central Luconia and their internal architecture suggest a development initiated and influenced by the late Neogene evolution of the South China Sea. A first regional fragmentation of an extensive carbonate bank probably took place in the early Mid-Miocene (20-15 Ma) period.